Analisis CSF, SWOT dan TOWS Studi Kasus: PT Intan Pariwara Klaten - Retnowati, Nurcahyani Dewi (Jurnal Buana Informatika, 2011)
Abstract. CSF, SWOT and TOWS Analysis, Case Study: PT Intan Pariwara Klaten. SWOT analysis identified the opportunity and the external threat as well as the strength and the internal weakness. The TOWS strategy matrix explain four types of the strategy that is the SO strategy (Strengths-Opportunities), the strategy WO (Weakness-Opportunities), the strategy St (Strengths-Threaths) and the WT strategy (Weakness-Threaths). In the CSF analysis (Critical Success Factor) was obtained by results that with the existence web interactive could become a development strategy of the marketing, the use of information technology could help the management of the company and the research of the consumers wish that it was felt needed to increase the companys profit. The threat that was dealt with by PT Intan Pariwara was depicted by the SWOT analysis, in part: more often sprang up the new publisher, the number of available publishers beforehand, and the buyer had the quite high tasteless strength. The strategy that could be taken by PT Intan Pariwara was depicted in the TOWS analysis. Keywords: Critical Success Factor, SWOT, TOWS Abstrak. Analisis SWOT mengidentifikasi peluang dan ancaman eksternal serta kekuatan dan kelemahan internal. Matriks strategi TOWS membantu manajer mengembangklan empat tipe strategi yaitu strategi SO (Strengths-Opportunities), strategi WO (Weakness-Opportunities), strategi ST (Strengths-Threaths) dan strategi WT (Weakness-Threaths). Pada analisis CSF (Critical Success Factor) didapatkan hasil bahwa dengan adanya web interaktif dapat menjadi suatu strategi pengembangan pemasaran, penggunaan teknologi informasi dapat membantu manajemen perusahaan dan riset keinginan konsumen yang dirasa perlu untuk meningkatkan profit perusahaan. Ancaman yang dihadapi oleh PT Intan Pariwara digambarkan oleh analisis SWOT, antara lain: semakin banyak bermunculan penerbit baru, banyaknya penerbit yang sudah ada sebelumnya, dan pembeli mempunyai kekuatan tawar yang cukup tinggi. Strategi yang dapat diambil oleh PT Intan Pariwara digambarkan dalam analisis TOWS. Kata Kunci: Faktor Penentu Kesuksesan, SWOT, TOWS